CENP-A overexpression promotes distinct fates in human cells, depending on p53 status - Daniel Jeffery (Nature Portfolio, 2021)
Jeffery et al. develop a system of inducible and reversible CENP-A overexpression, combined with a switch in p53 status in human cell lines. They find the tumor suppressor p53 as a key determinant of how CENP-A impacts cell state, cell identity and therapeutic response. This study suggests that CENP-A overexpression promotes the reprogramming of cell fates in the context of tumor evolution.